(untitled) (Journal of Tertiary Education and Learning, 2023)
The purpose of this study is to find out the factors which caused Chinese graduate students to study in Thailand during the COVID-19 pandemic. By analyzing 131 valid questionnaires obtained from current master’s degree students at Stamford International University in Thailand, the results revealed that most of the students were undergraduates from non-first-class institutions, worked in universities, and majored in arts. The factors for Chinese students to choose Thailand, from the highest scores to the lowest, were time factors, international relationships, learning pressure, and cultural inducement. Moreover, young teachers put much weight on learning pressure and cultural inducements. This study accordingly made two suggestions: 1. increasing the ways of further education for young teachers majored in arts; and 2. China may consider offering winter and summer master’s degree programs for in-service teachers.